2014
DOI: 10.1103/physrevb.89.144406
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the multiferroic switching inMnWO4

Abstract: The time dependence of switching multiferroic domains in MnWO4 has been studied by timeresolved polarized neutron diffraction. Inverting an external electric field inverts the chiral magnetic component within rise times ranging between a few and some tens of milliseconds in perfect agreement with macroscopic techniques. There is no evidence for any faster process in the inversion of the chiral magnetic structure. The time dependence is well described by a temperature-dependent rise time suggesting a well-defin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…Phenomenologically it has been demonstrated that a reorientation by acting on the improper (electric) order parameter tends to be slow with reversal times in the millisecond range 38,39 . By acting on the primary (magnetic) order parameter, theory predicts scenarios with a reversal within a few picoseconds, yet at so far unrealistically large fields 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Phenomenologically it has been demonstrated that a reorientation by acting on the improper (electric) order parameter tends to be slow with reversal times in the millisecond range 38,39 . By acting on the primary (magnetic) order parameter, theory predicts scenarios with a reversal within a few picoseconds, yet at so far unrealistically large fields 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Polycrystalline InTaO 4 was synthesized by a ceramic route starting from pre-dried In 2 transmission electron microscope operated at 200 KeV at the Servei Central de Suport a la Investigacio Experimental (SC-SIE) from Universitat de Valencia. It was also verified by powder XRD measurements, using Cu K α radiation, that the samples were single phased and presented the wolframitetype structure (P 2/c).…”
Section: Methodsmentioning
confidence: 99%
“…Ternary oxides of the form MTO 4 have been extensively studied for their interesting physical properties, in particular, those oxides crystallizing either in the scheelite or the wolframite structure [1][2][3][4][5][6][7][8][9][10]. During the last decade, the most studied members of this family of materials have been the orthotungstates and orthomolybdates, which have many technological applications [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…17 Another example is MnWO 4 , where electric polarization is generated by an elliptical spiral, 18 the chirality of which can be controlled by an electric field. 19 In Cr 2 O 3 , multiple co-existing mechanisms may even be possible.…”
Section: Pacs Numbersmentioning
confidence: 99%